The effect of thymus vulgaris extract and probiotic on growth performance, blood parameters, intestinal morphology, and litter quality of broiler chickens fed low-protein diets - Ali Golshahi; Mahmoud Shams Shargh; Behrouz Dastar; Enayat Rahmatnejad (Poultry Science)
This study investigated the effects of Thymus vulgaris extract (TVE) and probiotic (Protexin) on Arian broiler chickens fed low protein diets over 42 days. The 2 × 3 factorial experiment involved two dietary crude protein (CP) levels and three supplementations, each with five replicates of 10 birds. The CP levels included a control group and a low-CP group with 5% reduced CP content. The supplementations were: no additive, probiotic at 0.1 g/kg diet, and TVE at 1 ml/L drinking water. GC-MS analysis of TVE identified linalool (28.54%), carvacrol (20.22%), and thymol (7.07%) as key bioactive compounds. Low-CP diets increased feed intake (FI) and feed conversion ratio (FCR) during the grower period (P > 0.05). Additives boosted FI and body weight gain (BWG) during the starter period, with probiotics having a stronger effect (P < 0.05). TVE improved protein efficiency ratio (PER) and energy efficiency ratio (EER), while both TVE and probiotics enhanced European production efficiency factor (EPEF) to levels like normal-CP diets (P < 0.05). Intestinal morphology was unaffected by treatments (P > 0.05). Low-CP diets reduced serum albumin levels (P < 0.05). TVE lowered serum cholesterol and triglycerides, while probiotic reduced triglycerides (P < 0.05). TVE also decreased alkaline phosphatase (ALP), and probiotics reduced alanine transaminase (ALT) compared to control (P < 0.05). Cholesterol levels decreased with the normal diet combined with TVE, while TG levels were reduced with the diets combined with TVE and probiotics (P < 0.05). ALP and ALT levels dropped with low-CP × TVE and normal diet × probiotic, respectively (P < 0.05). Low-CP diets and TVE groups showed reduced litter nitrogen (P < 0.05). These results suggest that probiotics and TVE can alleviate the negative effects of low-CP diets on broiler performance. Additionally, probiotics and TVE improve blood biochemistry and litter quality in broiler chickens.